Caffeic acid phenethyl ester counteracts doxorubicin-induced chemobrain in Sprague-Dawley rats: Emphasis on the modulation of oxidative stress and neuroinflammation. (15th December 2020) - Ali, Marwa A.; Menze, Esther T.; Tadros, Marianne G.; Tolba, Mai F.
Abstract: Chemotherapy-induced cognitive dysfunction (chemobrain) is one of the major complaints for cancer patients treated with chemotherapy such as Doxorubicin (DOX). The induction of oxidative stress and neuroinflammation were identified as major contributors to such adverse effect. Caffeic acid phenethyl ester (CAPE) is a natural polyphenolic compound, that exhibits unique context-dependent antioxidant activity. It exhibits pro-oxidant effects in cancer cells, while it is a potent antioxidant and cytoprotective in normal cells. The present study was designed to investigate the potential neuroprotective effects of CAPE against DOX-induced cognitive impairment. Chemobrain was induced in Sprague Dawley rats via systemic DOX administration once per week for 4 weeks (2 mg/kg/week, i.p.). CAPE was administered at 10 or 20 μmol/kg/day, i.p., 5 days per week for 4 weeks. Morris water maze (MWM) and passive avoidance tests were used to assess learning and memory functions. Oxidative stress was evaluated via the colorimetric determination of GSH and MDA levels in both hippocampal and prefrontal cortex brain regions. However, inflammatory markers, acetylcholine levels, and neuronal cell apoptosis were assessed in the same brain areas using immunoassays including either ELISA, western blotting or immunohistochemistry. DOX produced significant impairment in learning and memory as indicated by the data generated from MWM and step-through passive avoidance tests. Additionally DOX-triggered oxidative stress as evidenced from the reduction in GSH levels and increased lipid peroxidation. Treatment with DOX resulted in neuroinflammation as indicated by the increase in NF-kB (p65) nuclear translocation in addition to boosting the levels of pro-inflammatory mediators (COX-II/TNF-α) along with the increased levels of glial fibrillary acid protein (GFAP) in the tested tissues. Moreover, DOX reduced acetylcholine levels and augmented neuronal cell apoptosis as supported by the increased active caspase-3 levels. Co-treatment with CAPE significantly counteracted DOX-induced behavioral and molecular abnormalities in rat brain tissues. Our results provide the first preclinical evidence for CAPE promising neuroprotective activity against DOX-induced neurodegeneration and memory deficits. Graphical abstract: Image 1 Highlights: Concurrent treatment with CAPE guarded against DOX-induced chemobrain. CAPE hampered DOX-induced oxidative imbalance in hippocampal and cortical tissues. CAPE suppressed DOX-mediated neuroinflammation. CAPE protected against DOX-induced neuronal cell apoptosis. CAPE replenished acetylcholine levels in hippocampal and cortical tissues.